2021
DOI: 10.1016/j.jbc.2021.100977
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of GPI2 suppresses glycosylphosphatidylinositol GlcNAc transferase activity and alters GPI glycan modification in Trypanosoma brucei

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 73 publications
2
10
0
Order By: Relevance
“…The TbGPI14 null parasites were viable but grew almost 2× more slowly than the parental cells (Figure 1a ). Reduced growth in culture has also been reported in T. brucei procyclic forms lacking other GPI synthesis enzymes (Hong et al., 2006 ; Jenni et al., 2021 ; Nagamune et al., 2000 , 2003 ; Verchère et al., 2021 ).…”
Section: Resultsmentioning
confidence: 79%
“…The TbGPI14 null parasites were viable but grew almost 2× more slowly than the parental cells (Figure 1a ). Reduced growth in culture has also been reported in T. brucei procyclic forms lacking other GPI synthesis enzymes (Hong et al., 2006 ; Jenni et al., 2021 ; Nagamune et al., 2000 , 2003 ; Verchère et al., 2021 ).…”
Section: Resultsmentioning
confidence: 79%
“…We recently reported that T. brucei procyclic forms lacking Tb GPI2 showed decreased viability on agarose plates (Jenni et al., 2021 ). To investigate whether Tb GPI8 was also required for survival on agarose plates, we determined the cell number and PDT in the presence and absence of tetracycline (Figure S5 , upper panels).…”
Section: Resultsmentioning
confidence: 99%
“…In all three GPI mutants, the surface is devoid of EP and GPEET procyclins (Güther et al., 2006 ; Lillico et al., 2003 ; Nagamune et al., 2004 ). As also seen with a procyclin null mutant (Vassella et al., 2003 ), deletion of Tb GPI8 (Lillico et al., 2003 ), Tb GPI10 (Nagamune et al., 2004 ) or Tb GPI2 (Jenni et al., 2021 ) in procyclic forms causes the accumulation of free (non‐protein‐linked) GPIs on the surface. This was not the case in Tb GPI12 null mutants, which did not express either procyclins or free GPIs on their surface (Güther et al., 2006 ).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The cell suspension was spread on a microscopy slide and left to adhere for at least 10 min. Trypanosomes were fixed in 4% (w/v) paraformaldehyde in 1x PBS for 10 min [52]. The slides were washed 3 times with PBS for 5 min each and subsequently permeabilized in 0.2% (w/v) Triton X-100 in PBS for 5 min.…”
Section: Fluorescence Microscopymentioning
confidence: 99%